Results of different treatments on a meadow near Aba - Takács, Anna; Wagenhoffer, Zsombor; Bajnok, Márta; Penksza, Károly; Saláta-Falusi, Eszter; Szentes, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2024)
In many cases, the use of different agrotechnical elements in our semi-natural fields must be coordinated to achieve agricultural and conservation objectives. The long-term preservation of the quality of pastures and meadows, and the most economical use of these and the cheapest possible keeping of animals, are essential for sustainable livestock farming. The studies were carried out on a wet grassland on the outskirts of Aba. The vegetation of 8 plots and the quantity and quality composition of the biomass produced were investigated. The effects on vegetation of the following treatments were analyzed I. aerated; II. loosened; III. aerated and loosened; IV. aeration and 15 t/ha manure; VI. loosened and 15 t/ha stable manure; VII. loosened, ventilated and 15 t/ha manure; VIII. loosened, aerated and 30 t/ha manure. 5 cenology recordings were made in each plot. Based on the species cover and height data, Klapp’s method was used to classify the grassland, as well as Balázs’s method, with the heights. The data showed that the species composition of each plot changed significantly compared to the control plot data. There is a direct correlation between the increase in coverage of the dominant grasses, in particular Festuca arundinacea, Dactylis glomerata, Alopecurus pratensis, Poa humilis and legumes (e.g. Lathyrus tuberosus, Lotus corniculatus) and the amount of nutrients applied. The data show that the application of the manure, combined with the aeration and loosening of the sward, resulted in a significant yield increase, which also represents a significant economic benefit. Fertilisation and aeration alone did not lead to significant yield gains. In addition, a baseline data set was obtained for the effects of other grassland management practices over the long term under the same environmental conditions.